Penerapan Alat Peniris Serbaguna Model Silinder Sistem Sentrifuse Untuk Meningkatkan Mutu Dan Higienis Produk Kerupuk Jagung Kelimutu Sikumana Kota Kupang - Muntasir, Muntasir; Purnawan, Sigit; Syahdan, Mustakim (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2018)
Science for Society in Small Industries of Corn Crackers Kelimutu Sikumana Kota Kupang in the form ofapplication of slicer has been implemented, one of the problems in the production of Kelimutu corn cracker is still a lot ofoil in frying product which only drained on simple sieve and placed some time above cardboard that can cause loweringquality and low hygiene, so it is necessary to do the reduction of frying oil products corn chips cracker. In order toincrease the added value and selling value of the product, it is necessary to synergy between Universities and Partners inthe form of science and technology for the community. The main constituent component of a slicer is a cylinder plate as abucket of a slicer, a cylinder slicer, an electric dynamo as a centrifuge system rotating motor and a load-bearingconstruction. The method of this program is the provision of materials, design and manufacture of tools, demonstrationtools and the provision of a versatile cylinder system centrifuge model by team, tool simulation, special counseling atpartner sites and suggestions as follow-up in production endurance. The output of this program can give the added valueof production increase from 20 kg-30 kg of raw material to 40 kg - 50 kg,  corn raw material after cooking, dried, fried,processed and packed into 60 - 100 packs per 500 g with price Rp . 15,000.00 per pack. Or equivalent Rp. 900,000.00 to Rp1,500,000.00 per production in the form of cash and consumptions, and non-greasy, clean, hybrid corn chip crackers